Nano-Biomaterials for the Delivery of Therapeutic and Monitoring Cues for Aortic Diseases - Zhu, Shichao; Zhu, Kai; Li, Jun; Lai, Hao; Wang, Chunsheng (Frontiers in Bioengineering and Biotechnology, 2020)
Aorta is the largest artery in the body, so any diseases or conditions which could cause damage to the aorta would put patients at considerable and life-threatening risk. In the management of aortic diseases, the major treatments include drug therapy, endovascular treatment and surgical treatment, which are of great danger or with a poor prognosis. The delivery of nano-biomaterials provides a potential development trend and an emerging field where we could monitor patients' conditions and responses to the nanotherapeutics. One of the putative applications of nanotechnology is ultrasensitive monitoring of cardiovascular markers by detecting and identifying aneurysms. Moreover, the use of nanosystems for targeted drug delivery can minimize the systemic side effects and enhance drug positioning and efficacy compared to conventional drug therapies. This review shows some examples of utilizing nano-biomaterials in in-vitro organ and cell culture experiments and explains some developing technologies in delivering and monitoring regenerative therapeutics.